Association between ethylene oxide exposure and serum sex hormone levels measured in a reference sample of the US general population - Wu, Wenhao; Wu, Jingna; Hou, Zebin; Yan, Qi; Qin, Kaixin; Zhao, Yuan; Zhang, Hua; Zhu, Yikun; He, Junhua; Li, Jin (Frontiers in Endocrinology, 2025)
Ethylene oxide (EO) is a crucial organic compound commonly utilized in industrial and medical products. Food and Drug Administration (FDA)-approved EO sterilization sterilizes about 50% of sterile medical devices in the U.S. Animal and human studies have suggested that EO exposure may result in severe health problem. However, studies evaluating the relationship between EO exposure and sex hormones in human populations are still lacking. Therefore, further investigation into EO’s effects on humans is essential. This cross-sectional study within the U.S. National Health and Nutrition Examination Survey (NHANES),2013–2016 examined the relationship between EO-hemoglobin adducts (HbEO) and sex hormones. HbEO was found to be inversely associated with estradiol (E2) and positively associated with the ratio of total testosterone (TT) to E2 and sex hormone-binding globulin (SHBG) levels in adult males. Such associations HbEO and E2 and SHBG were non-linear in male adults. However, no significant associations were found between HbEO and sex steroids across various age groups of females and all male age groups except for adults. Thus, our study provides evidence that EO may potentially serve as an endocrine disruptor in the environment, affecting the levels of sex hormones in adult males.